Complete Genome Sequence of Weissella cibaria NH9449 and Comprehensive Comparative-Genomic Analysis: Genomic Diversity and Versatility Trait Revealed - Surachat, Komwit; Kantachote, Duangporn; Wonglapsuwan, Monwadee; Chukamnerd, Arnon; Deachamag, Panchalika; Mittraparp-arthorn, Pimonsri; Jeenkeawpiam, Kongpop (Frontiers in Microbiology, 2022)
Lactic acid bacteria (LAB) in the genus Weissella spp. contain traits in their genome that confer versatility. In particular, Weissella cibaria encodes several beneficial genes that are useful in biotechnological applications. The complete genome of W. cibaria NH9449 was sequenced and an in silico comparative analysis was performed to gain insight into the genomic diversity among members of the genus Weissella. A total of 219 Weissella genomes were used in a bioinformatics analysis of pan-genomes, phylogenetics, self-defense mechanisms, virulence factors, antimicrobial resistance, and carbohydrate-active enzymes. These investigations showed that the strain NH9449 encodes several restriction-modification-related genes and a CRISPR-Cas region in its genome. The identification of carbohydrate-active enzyme-encoding genes indicated that this strain could be beneficial in biotechnological applications. The comparative genomic analysis reveals the very high genomic diversity in this genus, and some marked differences in genetic variation and genes among Weissella species. The calculated average amino acid identity (AAI) and phylogenetic analysis of core and accessory genes shows the possible existence of two new species in this genus. These new genomic insights into Weissella species and their biological functions could be useful in the food industry and other applications.